PRODUKTIVITAS DAN KESEHATAN AYAM BROILER PASCA LARANGAN ANTI GROWTH PROMOTERS DI INDONESIA - Sihombing, Dewi Elfrida; Fajri, Aulia Irhamni (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2024)
Antibiotic Growth Promoters (AGP) have been used in the broiler industry to improve growth performance. The use of AGPs over a long period of time has led to antibiotic-resistant bacteria. Therefore, the Indonesian government has banned the use of AGPs. This has led to the search for alternative strategies to maintain productivity and the health of broiler chickens. This review aims to examine the productivity and health of broiler chickens following the AGP ban and explore potential alternatives. The ban on AGPs has resulted in decreased productivity and increased mortality in broiler chickens. Several alternatives to AGPs have been proposed, including the use of natural growth promoters and the implementation of strict biosecurity measures. Natural growth promoters, such as plant extracts have shown promising results in improving growth performance and gut health in broiler chickens. The implementation of biosecurity measures can help to prevent and control diseases, thus reducing the need for antibiotics. In conclusion, the ban on AGPs has created challenges for the broiler industry in Indonesia. However, the use of natural growth promoters and the implementation of biosecurity measures offer potential solutions to maintain productivity and the health of broiler chickens.